A Redox‐Active Tetrazine‐Based Pincer Ligand for the Reduction of N‐Oxyanions Using a Redox‐Inert Metal. Issue 45 (2nd July 2021) - Beagan, Daniel M.; Maciulis, Nicholas A.; Pink, Maren; Carta, Veronica; Huerfano, I. J.; Chen, Chun‐Hsing; Caulton, Kenneth G.
Abstract: The reaction chemistry of the bis‐tetrazinyl pyridine ligand (btzp) towards nitrogen oxyanions coordinated to zinc is studied in order to explore the reduction of the NO x − substrates with a redox‐active ligand in the absence of redox activity at the metal. Following syntheses and characterization of (btzp)ZnX2 for X=Cl, NO3 and NO2, featuring O−Zn linkage of both nitrogen oxyanions, it is shown that a silylating agent selectively delivers silyl substituents to tetrazine nitrogens, without reductive deoxygenation of NO x −1 . A new synthesis of the highly hydrogenated H4 btzp, containing two dihydrotetrazine reductants is described as is the synthesis and characterization of (H4 btzp)ZnX2 for X=Cl and NO3, both of which show considerable hydrogen bonding potential of the dihydrotetrazine ring NH groups. The (H4 btzp)ZnCl2 complex does not bind zinc in the pincer pocket, but instead H4 btzp becomes a bridge between neighboring atoms through tetrazine nitrogen atoms, forming a polymeric chain. The reaction of AgNO2 with (H4 btzp)ZnCl2 is shown to proceed with fast nitrite deoxygenation, yielding water and free NO. Half of the H4 btzp reducing equivalents form Ag 0 and thus the chloride ligand remains coordinated to the zinc metal center to yield (btzp)ZnCl2 . To compare with AgNO2, experiments of (H4 btzp)ZnCl2 with NaNO2 result in salt metathesis between chloride and nitrite, highlighting the importance of a redox‐active cation in the reduction of nitrite to NO. Abstract : With or without zinc : A redox‐active ligand is shown to be active towards nitrite reduction to nitric oxide, with and without the presence of a coordinated electrophile, zinc. The pre‐reduced ligand stores four protons and four electrons in two reduced tetrazine arms, all of which are used in reactivity with silver nitrite.